HUBUNGAN EXPLOSIVE POWER OTOT LENGAN DAN BAHU DENGAN HASIL TOLAK PELURU SISWA SMPN 6 TELUK TENGAH KECAMATAN KUANTAN TENGAH - Juita, Ardiah; ', Al Hafiz; ', Drs. Ramadi., S.Pd., M.Kes AIFO (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, Background problem in this research is the result of shot put students are still many who do not reach the target. This is presumably because of the explosive power of arms and shoulders. Therefore, the purpose of this study was to determine whether there is a corelation explosive power of arms and shoulders with shot put results students of SMPN 6 Teluk Tengah District of Kuantan Tengah. This type of research is correlational comparing the measurement results of two different variables in order to determine the degree of correlation between these variables. As the independent variable (X) is explosive power and arm muscles while the dependent variable (Y) is the result of shot put. This empirically Data obtained from the tests using two hand medicine ball put and shot put test. Based on the results of research and data processing using statistical procedures of research, it can be concluded that for the corelation between the variables x and y values obtained r = 0.66 then r xy> rtabel (0.66> 0.361). And obtained the mean of 4.71 thitungsebesar thitung> ttabel (4.71> 1.701) so this shows that the variables X and Y there is a significant corelation, then Ho is rejected and Ha accepted.Keywords : Explosive Power Arm and Shoulder Muscles, Shot Put